All-solid-state lithium-ion battery positive electrode material and preparation method and application

The synthesis of LiFeCl3+S composite material through high-energy ball milling method has solved the interface problems and low energy density of all-solid-state lithium-ion battery positive electrode materials, achieved significant improvement in energy density and improved cycle stability, and has good industrial application prospects.

CN119315016BActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411834700.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The positive electrode materials of all-solid-state lithium-ion batteries have interface problems and low energy density, resulting in insufficient cycle stability and energy density of the battery system.

Method used

The LiFeCl3+S composite material is synthesized by high-energy ball milling method, providing four reaction platforms to improve the specific capacity and energy density of LiFeCl3, and to reduce the voltage difference by introducing S in situ, improving the adhesion and uniformity of the material.

Benefits of technology

The energy density of the cathode material has been improved by 50%-55%, cycle stability has been improved, and the process is simple and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315016B_ABST
    Figure CN119315016B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of all-solid-state lithium-ion batteries, and specifically relates to all-solid-state lithium-ion battery positive electrode materials, preparation methods and applications. Li2S and FeCl3 raw materials are taken and mixed evenly; under the protection of an inert atmosphere, the obtained raw materials are subjected to a high-energy ball milling reaction to obtain the positive electrode material. The high-energy-density multi-electron transfer positive electrode material described in the present invention only needs to be compounded with 5% conductive carbon and 25% supporting electrolyte to be applied to all-solid-state lithium-ion batteries. Compared with sulfur-based positive electrode materials, the proportion of active substances has obvious advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of all-solid-state lithium-ion batteries, and in particular relates to all-solid-state lithium-ion battery positive electrode materials, preparation methods and applications. Background Art

[0002] Based on the dual carbon goals, vigorously developing new energy vehicles is conducive to reducing carbon emissions and thus achieving the dual carbon goals. As a key factor in the promotion of new energy vehicles, the performance of its power battery has attracted much attention. Its power battery energy density and safety are currently lacking in competitiveness compared with traditional vehicles. In order to improve the safety and energy density of lithium-ion batteries, it is necessary to explore new battery systems. All-solid-state lithium batteries can directly match lithium metal negative electrodes to have high energy density, and replace traditional flammable organic electrolytes with non-flammable solid electrolytes, which greatly improves the safety of power batteries and is a key technology for realizing new energy vehicles in the future. In addition, all-solid-state lithium batteries have other advantages, including high lithium ion mobility, regular geometric shapes, simple battery design, and a wide operating temperature range.

[0003] However, the large weight of the positive electrode material and the low theoretical capacity are the key factors limiting the battery system from further improving its energy density. Based on this, this paper summarizes the two key problems existing on the positive electrode side of current solid-state lithium batteries, namely, interface problems and low energy density.

[0004] Interface problems are divided into interface contact problems and interface side reaction problems. The former is based on the high interface impedance caused by the solid-solid contact pores and grain boundaries in the positive electrode material itself, while the latter is due to additional side reactions generated by the direct contact between the positive electrode and the electrolyte under current, which will greatly reduce the cycle stability of the battery system.

[0005] The problem of low energy density can be divided into two reasons. First, the positive electrode material often needs to add supporting electrolytes and conductive carbon, resulting in the positive electrode active material accounting for only 50%, which greatly loses the energy density. On the other hand, multi-electron transfer and voltage platform restrict each other, that is, high-capacity multi-electron transfer reactions often correspond to low voltage platforms, while materials with high voltage platforms often have lower capacity.

[0006] In summary, it is particularly important to research and develop a multi-electron transfer positive electrode material that has a high voltage platform and high specific capacity, improves energy density and has good cycle stability. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention discloses an all-solid-state lithium-ion battery positive electrode material, preparation method and application. A halide positive electrode material with high energy density is synthesized by high-energy ball milling. At room temperature, after adding supporting electrolyte and conductive agent, it can be used in halide-based all-solid-state lithium-ion batteries. The LiFeCl3+S composite material is obtained by high-speed ball milling of Li2S+FeCl3, which provides four reaction platforms, increases the original specific capacity of LiFeCl3 by 35%-40%, and increases the energy density by 50%-55%; the S introduced in situ makes up for the voltage difference of nearly 2V from the transition of the LiFeCl3 deintercalation reaction platform to the conversion reaction platform, which is reduced to 1 V, making it more convenient for practical application; compared with the simple physical mixing of LiFeCl3 and S, the in-situ generation of S can better ensure the adhesion and uniformity of S near the LiFeCl3 particles; the prepared composite positive electrode material has a stable interface with the electrolyte, and the assembled all-solid-state battery shows good cycle stability.

[0008] In a first aspect, the present invention provides a method for preparing a positive electrode material for an all-solid-state lithium-ion battery, the method comprising the following steps:

[0009] Step 1), take Li2S and FeCl3 raw materials and mix them evenly;

[0010] Step 2) Under the protection of an inert atmosphere, the raw material obtained in step 1) is subjected to a high-energy ball milling reaction to obtain the positive electrode material.

[0011] Further, in step 1), Li2S is used as a lithium source and a sulfur source, and FeCl3 is used as an iron source and a chlorine source; the molar ratio of Li2S to FeCl3 is (0.25-1):1, preferably 0.5-0.8:1;

[0012] In step 2, the high-energy ball milling reaction comprises: placing the raw materials and ball milling beads into a ball milling jar, sealing it and filling it with an inert atmosphere, and then placing the ball milling jar in a high-energy ball mill for high-energy ball milling reaction;

[0013] The ratio of the total mass of the raw materials to the total mass of the ball milling beads is 1: (30-100), preferably 1: (70-75);

[0014] In the high-energy ball milling reaction, the ball milling speed is 1000-2000 rpm, preferably 1000-1200 rpm; the ball milling reaction time is 10-100 h, preferably 20-30 h.

[0015] Furthermore, the inert atmosphere is high-purity argon gas, the purity of the high-purity argon gas is greater than 99.999%, and the content of oxygen and water is less than 0.01 ppm.

[0016] In a second aspect, the present invention provides an all-solid-state lithium-ion battery positive electrode material prepared according to the above method.

[0017] In a third aspect, the present invention provides a use of the positive electrode material as a positive electrode active ingredient in a positive electrode of an all-solid-state lithium-ion battery.

[0018] In a fourth aspect, the present invention provides an all-solid-state lithium-ion battery composite positive electrode, wherein the all-solid-state lithium-ion battery composite positive electrode comprises the high energy density positive electrode material, a conductive agent and a supporting electrolyte.

[0019] Furthermore, the conductive agent includes one or more of carbon nanotubes, carbon nanofibers, graphene, SuperP, Ketjen black, acetylene black, and activated carbon, and the mass of the conductive agent accounts for 5%-10% of the total mass of the composite electrode; the supporting electrolyte includes one or two of Li2ZrCl6 and Li6PS5Cl, and the mass of the supporting electrolyte accounts for 20%-25% of the total mass of the composite electrode.

[0020] In a fifth aspect, the present invention provides an all-solid-state lithium-ion battery, wherein the all-solid-state lithium-ion battery comprises the all-solid-state lithium-ion battery composite positive electrode as a positive electrode.

[0021] The solid electrolyte of the all-solid-state lithium-ion battery is a double-layer stacked electrolyte composed of Li2ZrCl6 and Li6PS5Cl, and the negative electrode is a lithium metal foil.

[0022] The positive electrode of the present invention has four-stage reaction platforms with small voltage difference between the platforms, considerable energy density and good cycle stability.

[0023] The beneficial effects of the present invention are:

[0024] (1) The present invention prepares a multi-electron transfer cathode material with high energy density by high-energy ball milling. Compared with other chlorine-based cathode materials, the energy density has obvious advantages;

[0025] (2) The high energy density multi-electron transfer cathode material described in the present invention only needs to be compounded with 5% conductive carbon and 25% supporting electrolyte to be applied to all-solid-state lithium-ion batteries. Compared with sulfur-based cathode materials, the proportion of active substances has obvious advantages.

[0026] (3) Compared with LiFeCl3 material, the high energy density multi-electron transfer cathode material of the present invention reduces its original voltage difference of nearly 2 V to 1 V, significantly improves the energy density, and has good cycle stability;

[0027] (4) The high energy density multi-electron transfer cathode material described in the present invention is synthesized only by high-speed ball milling, which has a relatively simple process and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 SEM images of the positive electrode material Li2S+xFeCl3 (x=2) prepared in Example 2 and the positive electrode material LFSC prepared in Example 6;

[0029] Figure 2 X-ray diffraction spectra of the positive electrode materials Li2S+xFeCl3 (x=1, 2, 3, 4) prepared in Example 1, Example 2, Example 3, and Example 4;

[0030] Figure 3 TEM image of the positive electrode material prepared in Example 6;

[0031] Figure 4 The Raman signal test graphs of the positive electrode material Li2S+xFeCl3 (x=2) prepared in Example 2 and the material prepared in Comparative Example 1;

[0032] Figure 5 The Mössbauer spectrum of the positive electrode material Li2S+xFeCl3 (x=2) of Example 2;

[0033] Figure 6 The charge and discharge curves of the multi-electron transfer cathode materials prepared in Example 1, Example 2, Example 3, and Example 4 in a halide-based all-solid-state lithium-ion battery;

[0034] Figure 7 The charge and discharge curves of the high energy density multi-electron transfer cathode materials prepared in Examples 5, 6, 7 and 8 in halide-based all-solid-state lithium-ion batteries;

[0035] Figure 8 The charge and discharge curves of the composite positive electrode materials prepared for Comparative Examples 2 and 4 in halide-based all-solid-state lithium-ion batteries;

[0036] Fig. 9 The rate performance diagram of the positive electrode material prepared in Example 6 in a halide-based all-solid-state lithium-ion battery;

[0037] Fig.10 Cyclic performance diagram of positive electrode materials prepared for Example 6, Comparative Example 5 and Comparative Example 4 in halide-based all-solid-state lithium-ion batteries;

[0038] Fig.11 The charge and discharge curve diagram of the multi-electron transfer positive electrode material prepared in Example 9 in a halide-based all-solid-state lithium-ion battery. DETAILED DESCRIPTION

[0039] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0040] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0041] Synthesis of electrolyte

[0042] Synthesis of supporting electrolyte Li2ZrCl6: According to the formula 2LiCl+ZrCl4 molar ratio. Weigh 0.4 g dried LiCl and 1.1 g ZrCl4, put into a 100 mL zirconia ball mill, then add 110 g zirconia ball mill beads, and strictly seal the ball mill in the glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is: ball milling speed of 1000 rpm, ball milling reaction time of 24 h, and open the ball mill in the glove box every 4 hours for mixing. Finally, collect the material to obtain the electrolyte Li2ZrCl6;

[0043] Another Li6PS5Cl supporting electrolyte mentioned is commercially available from the Guolian Automotive Power Research Institute.

[0044] Example 1

[0045] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li2S+xFeCl3 (x=1, representing the molar number of FeCl3, based on the molar number of Li2S as 1), 0.331 g Li2S and 1.169 g anhydrous FeCl3 were weighed respectively; they were put into 100 mL zirconia ball milling jars respectively, and then 110 g zirconia ball milling beads were added to each ball milling jar, and the ball milling jars were strictly sealed in the glove box to ensure the argon inert dry atmosphere in the jars; the sealed ball milling jars were then placed in the ball mill and fixed; then the program was set for high-speed ball milling. The specific process of the high-energy ball milling reaction was as follows: the ball milling speed was 1000 rpm, the ball milling reaction time was 24 h, and the ball milling jars were opened in the glove box every 4 hours for mixing, and finally the materials were collected to prepare the cathode material Li2S+xFeCl3 (x=1).

[0046] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0047] Example 2

[0048] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li2S+xFeCl3 (x=2, representing the molar number of FeCl3, with the molar number of Li2S as 1), 0.186 g Li2S and 1.314 g anhydrous FeCl3 were weighed respectively; they were put into 100 mL zirconia ball milling jars respectively, and then 110 g zirconia ball milling beads were added to each ball milling jar, and the ball milling jars were strictly sealed in the glove box to ensure the argon inert dry atmosphere in the jars; the sealed ball milling jars were then placed in the ball mill and fixed; then the program was set for high-speed ball milling. The specific process of the high-energy ball milling reaction was as follows: the ball milling speed was 1000 rpm, the ball milling reaction time was 24 h, and the ball milling jars were opened in the glove box every 4 hours for mixing, and finally the materials were collected to prepare the cathode material Li2S+xFeCl3 (x=2).

[0049] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0050] Example 3

[0051] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li2S+xFeCl3 (x=3, representing the molar number of FeCl3, based on the molar number of Li2S as 1), 0.129 g Li2S and 1.371 g anhydrous FeCl3 were weighed respectively; they were put into 100 mL zirconia ball milling jars respectively, and then 110 g zirconia ball milling beads were added to each ball milling jar, and the ball milling jars were strictly sealed in the glove box to ensure the argon inert dry atmosphere in the jars; the sealed ball milling jars were subsequently placed in the ball mill and fixed; the program was then set for high-speed ball milling. The specific process of the high-energy ball milling reaction was as follows: the ball milling speed was 1000 rpm, the ball milling reaction time was 24 h, and the ball milling jars were opened in the glove box every 4 hours for mixing, and finally the materials were collected to prepare the cathode material Li2S+xFeCl3 (x=3).

[0052] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0053] Example 4

[0054] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li2S+xFeCl3 (x=4, representing the molar number of FeCl3, with the molar number of Li2S as 1), 0.099 g Li2S and 1.401 g anhydrous FeCl3 were weighed respectively; they were put into 100 mL zirconia ball milling jars respectively, and then 110 g zirconia ball milling beads were added to each ball milling jar, and the ball milling jars were strictly sealed in the glove box to ensure the argon inert dry atmosphere in the jars; the sealed ball milling jars were then placed in the ball mill and fixed; then the program was set for high-speed ball milling. The specific process of the high-energy ball milling reaction was as follows: the ball milling speed was 1000 rpm, the ball milling reaction time was 24 h, and the ball milling jars were opened in the glove box every 4 hours for mixing, and finally the materials were collected to prepare the cathode material Li2S+xFeCl3 (x=4).

[0055] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0056] Embodiment 5-8

[0057] Synthesis of high energy density multi-electron transfer cathode material: Weigh 0.14 g of each of the synthesized multi-electron transfer cathode materials in Examples 1-4, add 0.05 g of Li2ZrCl6 supporting electrolyte and 0.01 g of conductive agent (acetylene black), then add 110 g of zirconium oxide ball milling beads, and strictly seal the ball milling jar in the glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball milling jar in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 552 rpm; composite cathode materials can be prepared, and are recorded as Examples 5, 6, 7, and 8 from small to large according to x. Among them, for the convenience of description, Example 6 is called LFSC.

[0058] Example 9

[0059] According to the formula Li2S + 2FeCl3 (based on the molar number of Li2S as 1), 0.186 g Li2S and 1.314 g anhydrous FeCl3 were weighed and put into a 100 mL zirconia ball milling jar, and then 110 g zirconia ball milling beads were added to each jar, and the jar was strictly sealed in a glove box to ensure an argon inert dry atmosphere in the jar; the sealed jar was then placed in a ball mill and fixed; the program was then set for high-speed ball milling. The specific process of the high-energy ball milling reaction was a ball milling speed of 2000 rpm, a ball milling reaction time of 24 h, and finally the material was collected to prepare the cathode material precursor.

[0060] Weigh 0.14 g of the above-mentioned cathode material precursor, add 0.05 g of Li2ZrCl6 supporting electrolyte and 0.01 g of agent (acetylene black), put into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the mill; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 552 rpm; the multi-electron transfer cathode material can be prepared, which is recorded as LFSC-2000 rpm.

[0061] Comparative Example 1

[0062] Commercially available S (SIGMA-ALDRICH, 99.5%-100.5%) was weighed, evacuated and transferred to a glass bottle, which was then transferred to a glove box.

[0063] Comparative Example 2

[0064] Synthesis of LiFeCl4 cathode material: Weigh 0.311 g of dried LiCl and 1.189 g of anhydrous FeCl3 and put them all into a 100 mL zirconia ball mill, then add 110 g of zirconia ball mill beads, and strictly seal the ball mill in the glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in the ball mill and fix it; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is: ball milling speed 1000 rpm, ball milling reaction time 24 h. Open the ball mill in the glove box every 4 hours for mixing, and repeat 6 times to prepare the cathode material precursor.

[0065] Weigh 0.14 g of the sample obtained above (positive electrode material precursor), add 0.05 g Li2ZrCl6 supporting electrolyte and 0.01 g conductive agent (acetylene black), put all into a 100 mL ball mill, then add 110 g zirconia ball mill beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball mill speed of 552 rpm; the positive electrode material LiFeCl4 can be prepared.

[0066] Comparative Example 3

[0067] Synthesis of LiFeCl3 positive electrode material: 0.376 g of dried LiCl and 1.124 g of anhydrous FeCl2 were weighed and put into a 100 mL zirconia ball mill jar, and then 110 g of zirconia ball mill beads were added thereto. The ball mill jar was strictly sealed in a glove box to ensure an inert dry atmosphere of argon gas in the jar; the sealed ball mill jar was subsequently placed in a ball mill and fixed; the program was then set for high-speed ball milling. The specific process of the high-energy ball milling reaction was as follows: a ball milling speed of 1000 rpm and a ball milling reaction time of 24 h; the ball mill jar was opened in the glove box every 4 hours for mixing, and then repeated 6 times to prepare the positive electrode material precursor.

[0068] Comparative Example 4

[0069] Weigh 0.18 g of the sample (positive electrode material precursor) obtained in Comparative Example 3, add 0.02 g of conductive agent (acetylene black), and put all of it into a ball mill with a volume of 100 mL. Then, add 110 g of zirconia ball mill beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the mill. Subsequently, place the sealed ball mill in a ball mill and fix it. Then, perform low-speed ball milling at a ball milling speed of 180 rpm. The positive electrode material LiFeCl3 can be prepared.

[0070] Comparative Example 5

[0071] Preparation of LiFeCl3 simply mixed with S positive electrode material: According to the molar fraction of the formula 2LiFeCl3+S, weigh 1.370 g of sample 3 (LiFeCl3) and 0.130 g of sample 1 (S) of comparative example, and put all of them into a 100 mL zirconia ball mill, then add 110 g of zirconia ball mill beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then set the program for high-speed ball milling, the specific process of high-energy ball milling reaction is, ball milling speed 1000 rpm, ball milling reaction time 24 h; every 4 hours, open the ball mill in the glove box for mixing, and then repeat 6 times to prepare the positive electrode material precursor.

[0072] Then weigh 0.14 g of the precursor, add 0.05 g of Li2ZrCl6 supporting electrolyte and 0.01 g of conductive agent (acetylene black), and put all of them into a 100 mL zirconia ball mill jar, then add 110 g of zirconia ball mill beads, and strictly seal the ball mill jar in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill jar in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 552 rpm; collect the material to obtain 2LiFeCl3+S material.

[0073] Comparative Examples 6-7

[0074] According to the formula Li2S + 2FeCl3 (based on the molar number of Li2S as 1), the molar fraction ratio is calculated. Weigh 0.186 g Li2S and 1.314 g anhydrous FeCl3 respectively, put into a 100 mL zirconia ball mill, and then add 110 g zirconia ball mill beads to each ball mill. The two ball mills have the same materials, and the ball mills are strictly sealed in the glove box to ensure the argon inert dry atmosphere in the jar; then place the sealed ball mill in the ball mill and fix it; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is: the ball milling speed of comparative example 6 is 300 rpm, the ball milling reaction time is 24h, the ball milling speed of comparative example 7 is 1000 rpm, the ball milling reaction time is 4h, and finally collect the materials to prepare the positive electrode material.

[0075] All-solid-state lithium-ion battery assembly

[0076] A cylindrical battery mold with an inner diameter of 10 mm was used. First, 50 mg of the above-mentioned Li2ZrCl6 supporting electrolyte was added, and after maintaining a pressure of 0.5 t for 2 min, 50 mg of Li6PS5Cl supporting electrolyte was added, and a pressure of 1 t was maintained for 2 min. Then, 2.5 mg of positive electrode material (Examples 1-13, Comparative Examples 2, 4, and 5, respectively) was spread on the side of Li2ZrCl6, and an aluminum sheet was covered on the positive electrode material after flattening with tweezers, and a pressure of 4 t was maintained for 2 min. Then, a lithium sheet was added to the Li6PS5Cl side of the pressed battery core, and a copper sheet with the same diameter of 10 mm was added to the lithium sheet. Finally, the assembled battery core was placed in the mold, and a pressure of 0.5 t was maintained and tightened. An assembled all-solid-state lithium-ion battery can be obtained.

[0077] The prepared positive electrode materials and batteries were tested, and the results are as follows:

[0078] Experimental results analysis

[0079] Figure 1 From the SEM image, it can be observed that the positive electrode material Li2S+xFeCl3 (x=2) particles obtained in Example 2 are spherical and are composed of stacked small granular substances. This is due to the accumulation of LiFeCl3 and amorphous S. The amorphous sulfur element is evenly distributed near the LiFeCl3 accumulated particles and the two have good adhesion. The diameter of the large particles is 6~10 microns, and the particle size of Example 6 in which Li2ZrCl6 is added is slightly increased.

[0080] Figure 2 It was observed that the main peak positions of the samples in Examples 1, 2, 3, and 4 corresponded well to the LiFeCl3 crystal structure, proving that the high-speed ball milling method can react the two precursors Li2S and FeCl3 into this characteristic crystal structure.

[0081] Figure 3 df can be observed from the morphology of LFSC Example (6) of 500nm and nearly 100nm. From the outside, the surface of the particles is covered with a thin layer of amorphous sulfur, and the surface of the large particles is formed by the accumulation of stick-like particles LiFeCl3, which is consistent with the conclusion of the SEM image. Figure 3 The existence of (1 1 1) crystal plane can be clearly observed in ac, corresponding to 0.6 nm, and there are multiple disconnections, dislocations, and distortions on the surface, which corresponds to the non-periodic characteristics of halides obtained by mechanical ball milling. In addition, the (2 2 2) crystal plane corresponding to 0.3 nm and the (4 0 0) crystal plane corresponding to 0.26 nm can be observed. This is consistent with the conclusion of XRD.

[0082] Figure 4 The Raman test was carried out at 532 nm light with 5% light intensity and exposure for 60 s to measure the positive electrode material Li2S+xFeCl3 (x=2) prepared in Example 2; the material obtained in Comparative Example 1 was measured with 0.1% light intensity and exposure for 30 s. The Raman signal of LFSC corresponded well to the sublimated sulfur, proving that the high-speed ball milling process reaction caused the precursors Li2S and FeCl3 to be converted into S element.

[0083] Figure 5 The Mössbauer spectroscopy test proves that the iron in the positive electrode material Li2S+xFeCl3 (x=2) sample of Example 2 exists in the form of divalent iron. Figure 4 The Raman data shown prove that the high-speed ball milling process converts Li2S and FeCl3 into LiFeCl3 and S products.

[0084] Figure 6 The all-solid-state lithium-ion battery assembled with the positive electrode materials of Examples 1, 2, 3, and 4 was tested at 0.1 mA cm -2 The first three cycles of charge-discharge curve test showed that the charge-discharge curve had four electron transfer platforms, with a specific capacity of 200 mAh g -1 ~500 mAh g -1 interval.

[0085] Figure 7 The all-solid-state lithium-ion battery assembled with the positive electrode materials of Examples 5, 6, 7, and 8 was tested at 0.1 mA cm -2 In the first three cycles of the charge-discharge curve test, the charge-discharge curves of Examples 5, 6, and 8 all have a charge-discharge rate of more than 600 mAh g at this current. -1 The first cycle discharge capacity is significantly improved compared with Examples 1-4 and Comparative Example 4, among which Example 6 has the highest energy density, reaching about 1414 Whkg -1 .

[0086] Figure 8 The all-solid-state lithium-ion battery assembled with the cathode materials of Comparative Examples 2 and 4 was tested at 0.1 mA cm -2 From the first three cycles of the charge-discharge curve test, it can be observed that there is a voltage difference of about 1.7 V between the first discharge platform and the second discharge platform of this series of materials.

[0087] Examples 1-8 all present a new discharge platform in the range of 2.2 V-2.6 V. Compared with the materials of Comparative Examples 2 and 4, the platform voltage difference of up to 2 V is reduced to 1 V, which is beneficial to the application of battery systems in practical applications.

[0088] Fig. 9 The all-solid-state lithium-ion battery assembled with the positive electrode material of Example 6 was -1 , 0.2 mA cm -1 , 0.5 mA cm -1 , 1.0 mA cm -1 , 2.0 mA cm -1 , 0.1 mA cm -1 The rate performance test curve of charge and discharge cycle under current conditions, the material of Example 6 at 0.5 mA cm -1 The current still has about 400 mAh g -1 The discharge capacity of the cathode material is improved by utilizing the high capacity cathode material for practical application.

[0089] Fig.10 After Example 6 and Comparative Examples 4 and 5 were assembled into all-solid-state lithium-ion batteries, the -1 The current was run for three cycles and then increased to 0.3 mA cm -1 , a long cycle charge and discharge curve test was performed, and it was observed by comparison that Example 6 not only has a more obvious advantage in discharge capacity, but also has a very superior cycle stability. For example, the LiFeCl3 material of Comparative Example 4 has a capacity retention rate of about 55% after 250 cycles, while the capacity of the LFSC composite positive electrode of Comparative Example 4 drops to 0 after 250 cycles; the simple mixed 2LiFeCl3+S positive electrode of Comparative Example 5 can only cycle about 80 cycles before the capacity drops sharply, reflecting the advantages of the composite S positive electrode material method of the article.

[0090] Fig.11 Example 9 also achieved the charge-discharge curve effect of Example 6, proving the rationality of the ball milling speed of 1000-2000 rpm. However, due to the too low speed and ball milling time in Comparative Examples 6 and 7, Li2S has not yet completely reacted with FeCl3, and only achieved partial effects or did not participate in the reaction.

Claims

1. A method for preparing a positive electrode material for an all-solid-state lithium-ion battery, characterized in that: The method comprises the following steps: Step 1), take Li2S and FeCl3 raw materials in a molar ratio of (0.25-1):1, and mix them evenly; Step 2), under the protection of an inert atmosphere, subjecting the raw material obtained in step 1) to a high-energy ball milling reaction to obtain the positive electrode material; In the high-energy ball milling reaction, the ball milling speed is 1000-2000 rpm; the ball milling reaction time is 10-100 h; The positive electrode material is formed by the accumulation of LiFeCl3 and amorphous S.

2. The method for preparing the positive electrode material of an all-solid-state lithium-ion battery according to claim 1, characterized in that: In step 2), the high-energy ball milling reaction comprises: placing the raw materials and ball milling beads into a ball milling jar, sealing it and filling it with an inert atmosphere, and then placing the ball milling jar in a high-energy ball mill for high-energy ball milling reaction; The ratio of the total mass of the raw materials to the total mass of the ball milling beads is 1: (30-100).

3. The method for preparing the positive electrode material of an all-solid-state lithium-ion battery according to claim 1, characterized in that: The inert atmosphere is high-purity argon gas, the purity of the high-purity argon gas is greater than 99.999%, and the content of oxygen and water is less than 0.01 ppm.

4. An all-solid-state lithium-ion battery positive electrode material prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the all-solid-state lithium-ion battery positive electrode material according to claim 4 as a positive electrode active ingredient in an all-solid-state lithium-ion battery positive electrode.

6. An all-solid-state lithium-ion battery composite positive electrode, characterized in that: The all-solid-state lithium-ion battery composite positive electrode comprises the all-solid-state lithium-ion battery positive electrode material according to claim 4, and also comprises a conductive agent and a supporting electrolyte.

7. The all-solid-state lithium-ion battery composite positive electrode according to claim 6, characterized in that: The conductive agent includes one or more of carbon nanotubes, carbon nanofibers, graphene, SuperP, Ketjen black, acetylene black, and activated carbon, and the mass of the conductive agent accounts for 5%-10% of the total mass of the composite electrode; The supporting electrolyte includes one or two of Li2ZrCl6 and Li6PS5Cl; the mass of the supporting electrolyte accounts for 20%-25% of the total mass of the composite electrode.

8. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the all-solid-state lithium-ion battery composite positive electrode according to claim 6 as a positive electrode.

9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The solid electrolyte of the all-solid-state lithium-ion battery is a double-layer stacked electrolyte composed of Li2ZrCl6 and Li6PS5Cl, and the negative electrode is a lithium metal foil.

10. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The positive electrode has four reaction platforms.

Citation Information

Patent Citations

  • Doped phosphorus-sulfur iodide solid electrolyte and preparation method and application thereof

    CN111092262A

  • Halide-based positive electrode active material as well as synthesis method and application thereof

    CN116799201A

Cited By

  • A selenium-tellurium composite halide positive electrode material, a preparation method and application thereof

    CN122889742A